The Impact of Construction Supply Chain on the Implementation of Safety Management Systems - Othman, Norfaridatul Akmaliah; Ahmad Latiffi, Aryani; Jabar, Juhaini (Journal of Techno-Social, 2012)
The accident rate in the Malaysian construction industry is among the highest compared to other developing countries. The Malaysian government has recommended the self-regulation of safety management systems (SMS) for construction projects with the hope of improving the situation; however, the readiness of the local contractors to implement SMS is questionable. This research investigated the systemic issues of contractors in processing plants, during SMS development and implementation. Firstly, a literature review has surveyed the scenario of the construction supply chain as well as enabling an understanding of its impact on SMS implementation during project execution in the processing plants. Secondly, this paper has identified factors influencing SMS implementation through in-depth semi structured interview. Data were analyzed through grounded theory analysis method. The findings of this research appear to show that many obstacles encountered by contractors are interlinked, including cultural factors, working conditions and the organizational process.